BIOFILM FORMING CAPABILITY AND ANTIFUNGAL SUSCEPTIBILITY PROFILE OF Candida spp. FROM BLOOD - Rodrigues Costa, Carolina; Carneiro Nassiazene Lima Marreto, Lais; Lopes Rocha, Viviane; Cristina da Silva, Thaisa; do Rosário Rodrigues Silva, Maria (Revista de Patologia Tropical / Journal of Tropical Pathology, 2018)
Although Candida albicans remains the most frequent Candida species; however other species have emerged as important causes of candidiasis. Aims: In this work, we evaluated the in vitro susceptibility profile of C. albicans, C. parapsilosis, and C. tropicalis biofilms isolated from patients with candidemia to fluconazole, voriconazole, amphotericin B, and caspofungin. Differences between the biofilm ultrastructure of the three species were also determined. The isolates were phenotypically determined by growth on a ChromagarTM medium and assimilation profile on ID32C. The Scanning Electron Microscopy method (SEM) on biofilm was performed using polyurethane strips. For the in vitro susceptibility profile a microdilution in broth was used. Sessile cells were resistant to fluconazole, voriconazole and caspofungin. The resistance to amphotericin B was less pronounced and more variable between the tested isolates. In the SEM, slight differences in ultrastructural morphology for each species in biofilms were observed. Our results verified biofilm formation. Low susceptibility to the drugs in the three researched species confirmed the higher virulence of them.